2017
DOI: 10.1002/fam.2443
|View full text |Cite
|
Sign up to set email alerts
|

Study of using aluminum hypophosphite as a flame retardant for low‐density polyethylene

Abstract: Aluminum hypophosphite (AHP) was first used to improve the flame retardance of low‐density polyethylene (LDPE). The flame‐retardant properties of LDPE composites were investigated by the limiting oxygen index, vertical burning test (UL‐94), microscale combustion calorimetry, and cone calorimeter tests. The results showed that the incorporation of AHP could improve the flame retardancy of LDPE dramatically, the limiting oxygen index of LDPE containing 50 phr AHP reached 27.5%, and the UL‐94 could pass V‐0 ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…However, by reacting with the decamethylene diamine which has the electron-donating group, electron cloud density of P-O-C in DDP increased and the absorption peak of P-O-C moved to 1023 cm À1 . 23,[30][31][32] The FTIR spectra of PA6 and FRPA6-5 have been shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by reacting with the decamethylene diamine which has the electron-donating group, electron cloud density of P-O-C in DDP increased and the absorption peak of P-O-C moved to 1023 cm À1 . 23,[30][31][32] The FTIR spectra of PA6 and FRPA6-5 have been shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 7.64-8.53 (e) ppm, 3.48 (g) ppm, 3.24 (h) ppm and 1.62 (f) ppm account for the chemical shis of H on the diphenyl and methylene of DDP. To further conrm the chemical structure, 31 P-NMR spectra of DDP (deuterated DMSO as solvent) and FRPA6-5 were observed and shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the maximum weight loss rate (T max ) of neat TPU is 420°C and that of the TPU/25AHP composite is 322°C, corresponding to the dramatic peak in DTG curves. The reduced degradation temperature of the TPU/AHP composites is mainly due to the decomposition of AHP at low temperature . Additionally, the T 5% , T 10% , and T max values of the samples with AHP and PT are also lower than those of neat TPU, as shown in Table .…”
Section: Resultsmentioning
confidence: 87%
“…With the high thermal and chemical stabilities, good mechanical, and environmental friendly properties, aluminum hypophosphite (AHP) has attracted much attention over the decades . Gu et al found the addition of AHP to poly (lactic acid) (PLA) could markedly increase the LOI values.…”
Section: Introductionmentioning
confidence: 99%